Physiological, biochemical and endocrine responses of goat kids maintained on two different floor types in hot-dry weather conditions - SINGH, S P; RAMACHANDRAN, N; TRIPATHI, M K; BHUSAN, SAKET (The Indian Journal of Animal Sciences, 2017)
This study investigated physiological, biochemical and endocrine responses along with nutrient intake and growth of goat kids kept on either wooden slatted or soil floor in hot-dry weather conditions. Twenty kids (age 208 ±1.7 days; live weight 26.2±0.6 kg) were divided into two equal groups and allotted to either soil or slatted floor. After 14 days of adaptation, physiological responses, serum metabolites, enzymes and hormones were estimated at weekly intervals for 28 days. All the physiological responses increased from morning to afternoon with increase in temperature-humidity index. Type of flooring did not significantly influence physiological and growth variables. The serum biochemical, enzyme and endocrine responses were similar between both the groups. Due to lack of significant effect of slatted floor on growing kids, the provision of such floor in goat shelter could be appropriate only if it is economically feasible in terms of initial inputs and labour cost in hot-dry tropical environment.